(METH)acrylic resin film, adhesive sheet, and polarization film
Patent Information
- Application Number
- JP2024204459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2040-08-11
AI Technical Summary
【0022】 本発明によれば、薄い膜厚の樹脂フィルムを得るための溶液キャスト法に使用できる(メタ)アクリル系樹脂組成物であって、製膜した樹脂フィルム等の成形品が耐折性、耐切性、伸び性、耐溶剤性に優れている(メタ)アクリル系樹脂組成物、及び(メタ)アクリル系樹脂フィルムを提供することができる。 なお、本発明では、耐溶剤性の試験方法として、(メタ)アクリル系樹脂フィルムの試験片を、溶剤の液中に所定時間に渡り浸漬した後、前記溶剤に溶出しないで不溶分(残渣)として残った(メタ)アクリル系樹脂フィルムの割合(いわゆる、ゲル分率)を測定し、耐溶剤性を試験した。 また、従来技術の溶融押出法により(メタ)アクリル系樹脂フィルムを製膜する場合は、樹脂フィルムを製膜した後に、1軸又は2軸の延伸加工を施さない限り膜厚を40μm以下とすることができなかった。一方、本発明の(メタ)アクリル系樹脂組成物を用いれば、溶液キャスト法のみを用いて、膜厚が40μm以下である薄膜の(メタ)アクリル系樹脂フィルムを製造することができ、製造工程がより簡便になると共に、製造装置の費用低減を図ることができる。
Smart Images

Figure 2025033017000001 
Figure 2025033017000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a (meth)acrylic resin composition that is suitably used for forming a (meth)acrylic resin film, etc., and a (meth)acrylic resin film using the same. [Background technology]
[0002] 2. Description of the Related Art Since (meth)acrylic resin films have excellent transparency, heat processability, weather resistance, and chemical resistance, they have traditionally been used as resin films for surface coating of various equipment parts such as electronic devices, home appliances, automobile interior / exterior parts, and building materials. Moreover, in recent years, (meth)acrylic resin films have been used as optical films because of their excellent transparency, weather resistance, and the like.
[0003] Conventionally, the method of producing a (meth)acrylic resin film (PMMA film) made of polymethyl methacrylate (PMMA) resin has been the melt extrusion method, which is highly productive.
[0004] For example, Patent Document 1 discloses an acrylic resin film that can be suitably used for a member that integrates an acrylic resin film with a molded resin, and is particularly suitable for forming a surface protective layer as a paint replacement. The acrylic resin film according to the invention described in Patent Document 1 combines specific types of ultraviolet absorbers and lubricants to be added to the acrylic resin film, and these components are contained in specific amounts. For this reason, Patent Document 1 states that the film can be suitably used as a paint replacement acrylic resin film used for forming a surface protective layer.
[0005] Patent Document 2 discloses a method for improving the impact resistance, which is an essential drawback of acrylic resins, without including a rubber-containing graft copolymer, which causes the loss of the unique beautiful color tone and transparency, which are the advantages of acrylic resins. The acrylic resin composition according to the invention described in Patent Document 2 is said to be able to solve the problem that, when the melt extrusion temperature is increased during the melt extrusion process of forming the resin composition into a film, the decomposition gas or bleed-out product generated by the thermal decomposition of the graft copolymer contaminates cooling rolls such as a casting roll, resulting in a drop in productivity. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-286960 A [Patent Document 2] International Publication No. 2016 / 139927 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, the acrylic resin film according to the invention described in Patent Document 1 is produced by a melt extrusion method in which a mixture of an acrylic resin composition containing a thermoplastic polymer is kneaded in a degassing twin-screw extruder to obtain pellets of the acrylic resin composition, and then the molten resin composition is extruded into a T-die in a melt extruder. In addition, in Examples 1 to 6 described in Patent Document 1, acrylic resin films having a thickness of 50 to 125 μm are obtained. However, since the acrylic resin film according to the invention described in Patent Document 1 is a resin film produced by a melt extrusion method, there is a problem in that it is difficult to obtain a thin resin film having a thickness of 40 μm or less.
[0008] In addition, the acrylic resin composition according to the invention described in Patent Document 2 has a problem that the process for obtaining the graft copolymer requires a long time because the graft copolymer is gradually completed through 3 to 4 stages of graft polymerization reaction. In addition, in Examples 6 to 8 of Patent Document 2, in which an acrylic resin film was produced by melt extrusion, the thickness of the acrylic resin film obtained without stretching was 80 μm, and a thin resin film having a thickness of 40 μm or less was not obtained without stretching.
[0009] In this situation, there has been a demand for a method for forming a PMMA resin film by a solution casting method, which is a simpler resin film formation method than the melt extrusion method and has the advantage of being able to form thin films. The present inventors have intensively studied a method for forming a PMMA resin film by a solution casting method. As a result, they have found that by using a specific PMMA resin composition, a PMMA resin film having excellent physical properties equal to or greater than those of a film formed by a melt extrusion method can be obtained even when the film is formed by the solution casting method, and have been able to complete the present invention.
[0010] In the case of a method for forming a (meth)acrylic resin film by a conventional melt extrusion method, it was difficult to thin the film to a thickness of 40 μm or less. On the other hand, in the case of a method for forming a (meth)acrylic resin film by a solution casting method, it was possible to thin the film to a thickness of 40 μm or less, but there was a problem that it was difficult to improve the solvent resistance performance as a physical property of the obtained (meth)acrylic resin film. In addition, in the solution casting method, it is necessary to make the weight average molecular weight of the uncrosslinked PMMA resin contained in the (meth)acrylic resin composition a large value of 1 million or more, so that the solution of the (meth)acrylic resin composition has a high viscosity, and there was a problem that the workability in the film formation process was poor.
[0011] The present invention aims to provide a (meth)acrylic resin composition that can be used in a solution casting method for obtaining a thin resin film, and which provides a molded article such as a resin film having excellent folding resistance, cut resistance, elongation and solvent resistance, and a (meth)acrylic resin film. Various physical properties of the formed (meth)acrylic resin film can be determined, for example, by measuring the "number of folding times" for "folding resistance", by measuring the "tensile breaking strength" for "cut resistance", by measuring the "breaking elongation" for "extensibility", by measuring the "breaking elongation" for "elongation", and by measuring the "gel fraction" for "solvent resistance". [Means for solving the problem]
[0012] As a result of intensive research to solve the above problems, the present inventors have found that a (meth)acrylic resin composition containing a (meth)acrylic polymer, a rubber compound, and a crosslinking agent, the (meth)acrylic polymer being a copolymer of MMA (methyl methacrylate), an alkyl (meth)acrylate other than the MMA, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14, and at least one copolymerizable monomer having a functional group, copolymerized in a specific ratio, provides a (meth)acrylic resin film obtained by a solution casting method using such a (meth)acrylic resin composition, and is excellent in folding resistance, cut resistance, elongation, and solvent resistance, and is particularly improved in folding resistance and elongation, thereby completing the present invention. That is, the technical idea of the present invention is to obtain a (meth)acrylic resin film consisting of a resin layer crosslinked from a (meth)acrylic resin composition containing a specific (meth)acrylic polymer, a rubber compound, and a crosslinking agent, by a solution casting method.
[0013] In order to solve the above-mentioned problems, the present invention provides a (meth)acrylic resin composition containing a (meth)acrylic polymer, a rubber compound, and a crosslinking agent, wherein the (meth)acrylic polymer is a (meth)acrylic polymer consisting of a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, obtained by copolymerizing (A) 80 parts by weight or more of methyl methacrylate, 100 parts by weight of a total of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or more and the alkyl group has a carbon number of C1 to C14, and (B) 1.0 to 20.0 parts by weight of a total of at least one copolymerizable monomer having a functional group capable of reacting with the crosslinking agent, and the (meth)acrylic resin composition contains 1.0 to 25.0 parts by weight of the rubber compound relative to 100 parts by weight of the total of (A).
[0014] The (meth)acrylic polymer is preferably a (meth)acrylic polymer consisting of a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, obtained by copolymerizing (A) 80 to 99 parts by weight of methyl methacrylate, 1 to 20 parts by weight of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14, in a total of 100 parts by weight, and (B) 1.0 to 20.0 parts by weight of at least one monomer selected from a monomer group consisting of a copolymerizable monomer having a hydroxyl group and a copolymerizable monomer having a carboxyl group, as a copolymerizable monomer having a functional group capable of reacting with the crosslinking agent.
[0015] The crosslinking agent is preferably at least one selected from the group consisting of epoxy compounds, aziridine compounds, and isocyanate compounds.
[0016] It is preferable that the rubber compound is a core-shell particle formed of a rubber layer mainly made of SBR or butadiene in the core portion and an acrylic layer mainly made of methyl methacrylate in the shell portion, and that the volume-based average particle diameter of the core-shell particle is 0.05 to 2.0 μm.
[0017] It is preferable that the copolymerizable monomer having a hydroxyl group is at least one selected from the group of compounds consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide, and also includes at least one selected from the group of compounds consisting of 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0018] The present invention also provides a (meth)acrylic resin film having a thickness of 10 to 50 μm, which is a resin layer formed by crosslinking the (meth)acrylic resin composition, wherein the (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less and a haze value of 3.0% or less.
[0019] The present invention also provides a (meth)acrylic resin film which is a resin layer formed by crosslinking the (meth)acrylic resin composition, characterized in that the (meth)acrylic resin film has a gel fraction of 90% or more as a solvent resistance, a folding endurance (JIS P8115) of 100 or more as a folding resistance, and a breaking elongation of 10% or more as an extensibility.
[0020] The present invention also provides a pressure-sensitive adhesive sheet, characterized in that it comprises a pressure-sensitive adhesive layer formed on one or both sides of a (meth)acrylic resin film, which is a resin layer formed by crosslinking the (meth)acrylic resin composition.
[0021] The present invention also provides a polarizing film, characterized in that a (meth)acrylic resin film, which is a resin layer obtained by crosslinking the (meth)acrylic resin composition, is formed on one or both sides of a polarizer. Effect of the Invention
[0022] According to the present invention, it is possible to provide a (meth)acrylic resin composition that can be used in a solution casting method for obtaining a thin resin film, and the formed article, such as a resin film, has excellent folding resistance, cut resistance, elongation and solvent resistance, and a (meth)acrylic resin film. In the present invention, the solvent resistance was tested by immersing a test piece of a (meth)acrylic resin film in a solvent liquid for a predetermined time, and then measuring the proportion of the (meth)acrylic resin film that was not dissolved in the solvent and remained as an insoluble portion (residue) (so-called gel fraction). Furthermore, when a (meth)acrylic resin film is formed by the melt extrusion method of the prior art, it is impossible to obtain a film thickness of 40 μm or less unless the resin film is subjected to uniaxial or biaxial stretching after it is formed. On the other hand, when the (meth)acrylic resin composition of the present invention is used, a thin (meth)acrylic resin film having a film thickness of 40 μm or less can be produced by only a solution casting method, which simplifies the production process and reduces the cost of the production equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the present invention will be described based on preferred embodiments.
[0024] The (meth)acrylic resin composition of the present embodiment is a (meth)acrylic resin composition containing a (meth)acrylic polymer, a rubber compound, and a crosslinking agent, wherein the (meth)acrylic polymer is a (meth)acrylic polymer consisting of a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, obtained by copolymerizing (A) 80 parts by weight or more of methyl methacrylate, 100 parts by weight of a total of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or more and the alkyl group has a carbon number of C1 to C14, and (B) 1.0 to 20.0 parts by weight of a total of at least one copolymerizable monomer having a functional group capable of reacting with the crosslinking agent, and the (meth)acrylic polymer is characterized in that the rubber compound is contained in a ratio of 1.0 to 25.0 parts by weight relative to the total 100 parts by weight of the (A).
[0025] The (meth)acrylic polymer used in the (meth)acrylic resin composition of the present embodiment is preferably a (meth)acrylic polymer mainly composed of an alkyl (meth)acrylate having an alkyl group with carbon number of C1 to C14, particularly methyl methacrylate (MMA). The alkyl group of the alkyl (meth)acrylate may be either acyclic (straight-chain, branched) or cyclic (monocyclic, polycyclic). The (meth)acrylic polymer is preferably a copolymer containing at least two or more alkyl (meth)acrylates having an alkyl group with carbon number of C1 to C14. The (meth)acrylic polymer is preferably a copolymer having a homopolymer Tg of 0°C or higher and copolymerized with at least one or more alkyl (meth)acrylates having an alkyl group with carbon number of C1 to C14. Here, the main component of the (meth)acrylic polymer means a compound that occupies 50% by weight or more of the (meth)acrylic polymer by itself, or a group of compounds that occupy 50% by weight or more of the (meth)acrylic polymer by itself in total by two or more. That is, the main component accounts for 50 parts by weight or more of 100 parts by weight of the (meth)acrylic polymer. In the following description, when the Tg of a monomer is simply mentioned, it may refer to the Tg of a homopolymer.
[0026] In the (meth)acrylic polymer, the alkyl (meth)acrylate having a homopolymer Tg of 0° C. or higher and an alkyl group carbon number of C1 to C14 may be one or more selected from the group consisting of methyl (meth)acrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, s-butyl methacrylate, t-butyl (meth)acrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. Here, (meth)acrylate means at least one of acrylate and methacrylate.
[0027] In the (meth)acrylic polymer, the alkyl(meth)acrylate having a homopolymer Tg of 0° C. or higher and an alkyl group having a carbon number of C1 to C14 is preferably an alkyl(meth)acrylate having an alkyl group having a carbon number of C1 to C6, and more preferably an alkyl(meth)acrylate having an alkyl group having a carbon number of C1 to C4. Among the alkyl(meth)acrylates having an alkyl group having a carbon number of C1 to C4 other than methyl methacrylate, one or more selected from the group consisting of methyl acrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, s-butyl methacrylate, t-butyl acrylate, and t-butyl methacrylate are particularly preferred.
[0028] In the (meth)acrylic polymer, out of 100 parts by weight of (A) methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer Tg of which is 0°C or higher and the alkyl group has a carbon number of C1 to C14, it is preferable that the total of 80 parts by weight or more of methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer Tg of which is 0°C or higher and the alkyl group has a carbon number of C1 to C14 is 20 parts by weight or less, and it is more preferable that the total of 80 to 99 parts by weight of methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer Tg of which is 0°C or higher and the alkyl group has a carbon number of C1 to C14 is 1 to 20 parts by weight.
[0029] The (meth)acrylic polymer preferably contains 1.0 to 20.0 parts by weight of at least one copolymerizable monomer having a functional group capable of reacting with the (B) crosslinking agent, more preferably 1.0 to 12.0 parts by weight, and particularly preferably 1.0 to 9.0 parts by weight, per 100 parts by weight of the (A) methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14.
[0030] The copolymerizable monomer having a functional group capable of reacting with the (B) crosslinking agent may be at least one monomer selected from the group of monomers consisting of copolymerizable monomers having a hydroxyl group and copolymerizable monomers having a carboxyl group. The copolymerizable monomer having a functional group capable of reacting with the (B) crosslinking agent may be only a copolymerizable monomer having a hydroxyl group, only a copolymerizable monomer having a carboxyl group, or both a copolymerizable monomer having a hydroxyl group and a copolymerizable monomer having a carboxyl group may be used in combination.
[0031] The copolymerizable monomer having a hydroxyl group is preferably at least one selected from the group consisting of hydroxyalkyl (meth)acrylates and hydroxyl group-containing (meth)acrylamides. Specifically, the copolymerizable monomer having a hydroxyl group is preferably at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0032] In addition, it is preferable that the copolymerizable monomer having a hydroxyl group includes at least one selected from the group consisting of 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0033] The copolymerizable monomer having a carboxyl group is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, 2-(meth)acryloyloxyethyl tetrahydrophthalic acid, and the like.
[0034] The acrylic polymer preferably contains, as a copolymerizable monomer having a functional group capable of reacting with the (B) crosslinking agent, at least one monomer selected from a monomer group consisting of a copolymerizable monomer having a hydroxyl group and a copolymerizable monomer having a carboxyl group in a total amount of 1.0 to 20.0 parts by weight, more preferably 1.0 to 12.0 parts by weight, and particularly preferably 1.0 to 9.0 parts by weight, per 100 parts by weight of the (A) methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14.
[0035] The method for producing the acrylic polymer is not particularly limited, and a known polymerization method such as a solution polymerization method or an emulsion polymerization method can be used as appropriate. The acrylic polymer is preferably a copolymer having a weight average molecular weight of more than 100,000 and not more than 1,000,000, more preferably a copolymer having a weight average molecular weight of more than 100,000 and not more than 950,000, and particularly preferably a copolymer having a weight average molecular weight of more than 100,000 and not more than 900,000. If the weight average molecular weight of the acrylic polymer is 100,000 or less, it is difficult to obtain a molded product such as a (meth)acrylic resin film having excellent physical properties even if the (meth)acrylic resin composition is crosslinked. If the weight average molecular weight of the acrylic polymer is more than 1,000,000, the solution of the (meth)acrylic resin composition becomes highly viscous, and the workability of the film formation process is poor.
[0036] The crosslinking agent may be a compound having a crosslinkable functional group capable of undergoing a crosslinking reaction with a functional group of the (meth)acrylic polymer. From the viewpoint of storage stability of the (meth)acrylic resin composition, the crosslinking agent is preferably a compound that does not easily undergo a crosslinking reaction at room temperature (generally 5 to 35° C.) but initiates a crosslinking reaction when heated to a predetermined temperature or higher.
[0037] The crosslinking agent is preferably one or more selected from the group consisting of epoxy compounds, aziridine compounds, and isocyanate compounds. The (meth)acrylic resin composition of the present embodiment preferably contains 0.01 to 10 parts by weight of the crosslinking agent per 100 parts by weight of the total of the (A) methyl methacrylate and at least one or more alkyl (meth)acrylates other than the methyl methacrylate, the homopolymer of which has a Tg of 0° C. or higher and the alkyl group has a carbon number of C1 to C14.
[0038] The crosslinking agent (epoxy-based crosslinking agent) made of the epoxy compound is not particularly limited as long as it is a bifunctional or higher epoxy compound, and examples thereof include at least one selected from the group consisting of polyglycidyl ethers of polyols (including diols, glycols, and bisphenols), diglycidyl esters of dicarboxylic acids, diglycidyl-substituted amines, and tetraglycidyl-substituted diamines.
[0039] Among the epoxy-based crosslinking agents, examples of polyglycidyl ethers of polyols include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, resorcinol diglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether. Examples of diglycidyl esters of dicarboxylic acids include diglycidyl adipic acid ester and diglycidyl phthalate ester. Examples of diglycidyl-substituted amines include N,N-diglycidylaniline and N,N-diglycidyltoluidine. Furthermore, examples of tetraglycidyl-substituted diamines include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-m-xylylenediamine.
[0040] The crosslinking agent (aziridine crosslinking agent) made of the aziridine compound is not particularly limited as long as it is a bifunctional or higher aziridine compound, or a compound having two or more aziridine functional groups in one molecule. Examples of the aziridine functional group include a 1-aziridinyl group [-N(CH2)2], a 2-aziridinyl group, and a substituted aziridinyl group having a substituent such as a methyl group. Specific examples of the aziridine crosslinking agent include the following (1) to (2) addition products of a polyisocyanate compound and aziridine, the following (3) to (4) addition products of a polyol polyacrylate compound and aziridine, and the following (5) to (7) other polyacridine compounds.
[0041] (1) 4,4'-Bis[(1-aziridinyl)carbonylamino]diphenylmethane (CH2)2NCONH-C6H4CH2C6H4-NHCON(CH2)2 (2) 1,6-Bis[(1-aziridinyl)carbonylamino]hexane (CH2)2NCONH-(CH2)6-NHCON(CH2)2 (3) Trimethylolpropane-tris[2-(1-aziridinyl)propionate] CH3CH2C[CH2O-COCH2CH2N(CH2)2]3 (4) Tetramethylolmethane-tris[2-(1-aziridinyl)propionate] HOCH2C[CH2O-COCH2CH2N(CH2)2]3 (5) Tris(1-aziridinyl)phosphine oxide O=P[N(CH2)2]3 (6) Tris(1-aziridinyl)phosphine sulfide S = P[N(CH2)2]3 (7) 2,4,6-Tris(1-aziridinyl)-1,3,5-triazine (C3N3)[N(CH2)2]3
[0042] Examples of the crosslinking agent (isocyanate-based crosslinking agent) made of the isocyanate compound include at least one selected from the group of compounds consisting of bifunctional isocyanates (diisocyanate compounds) such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), and trifunctional or higher polyisocyanate compounds such as biuret modified compounds, isocyanurate modified compounds, and adducts thereof. Here, examples of the trifunctional or higher adducts include adducts of a diisocyanate compound and a trivalent or higher polyol such as trimethylolpropane or glycerin.
[0043] The (meth)acrylic resin composition contains a rubber compound as an essential component in addition to a (meth)acrylic polymer and a crosslinking agent for crosslinking the (meth)acrylic polymer. The (meth)acrylic resin composition of the present embodiment preferably contains 1.0 to 25.0 parts by weight, more preferably 3.0 to 20.0 parts by weight, of the rubber compound per 100 parts by weight of the total of the (A) methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0° C. or higher and the alkyl group has a carbon number of C1 to C14.
[0044] The rubber compound is not particularly limited as long as it is a polymer that exhibits rubber-like elasticity, but a rubber compound that has excellent dispersibility or miscibility with the (meth)acrylic polymer is preferred. For example, a rubber compound made of a vinyl polymer such as an olefin elastomer, a styrene elastomer, an acrylic elastomer, an acrylic rubber, a nitrile rubber, a butadiene rubber, a polyisoprene rubber, or a natural rubber is preferred. The rubber compound may be a copolymer made of a hard segment and a soft segment, and may be a block copolymer having at least three blocks, such as (hard segment)-(soft segment)-(hard segment).
[0045] The rubber compound is preferably crosslinked by physical or chemical crosslinking. The physical crosslink is not particularly limited as long as it is a crosslink caused by an interaction not based on a covalent bond, and is not limited to, for example, a hydrogen bond, a hydrophobic bond, etc. In the case of a physical crosslink, the crosslinking point is fixed at room temperature, and the bond is dissociated at a high temperature, so that the rubber compound can exhibit thermoplasticity. For chemical crosslinking, a compound having a functional group such as a vinyl group, an epoxy group, or an isocyanate group is used as a crosslinking monomer or a crosslinking agent. A crosslinking polymer may be synthesized by copolymerizing a crosslinking monomer with a non-crosslinking monomer. A crosslinking polymer may be synthesized by reacting a crosslinking agent with a non-crosslinking polymer obtained from a non-crosslinking monomer. Crosslinking of a non-crosslinking polymer can also be performed by introducing a covalent bond into the polymer using a radical generator such as a peroxide, an energy ray such as ultraviolet light, or the like.
[0046] Examples of the olefin-based elastomer include aliphatic olefin copolymers such as propylene-ethylene copolymer, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, propylene-ethylene-1-butene copolymer, and propylene-1-butene copolymer. Examples of the styrene-based elastomer include styrene-butadiene copolymers such as styrene-butadiene rubber (SBR), aromatic olefin-aliphatic olefin copolymers such as styrene-isoprene copolymers and styrene-ethylene copolymers. Examples of the acrylic elastomer include a (meth)acrylic acid ester-acrylonitrile copolymer, a (meth)acrylic acid ester-ethylene copolymer, and an acrylic acid ester-methacrylic acid ester block copolymer.
[0047] Examples of the acrylic rubber include an acrylic acid ester-acrylonitrile copolymer and an acrylic acid ester-chloroethyl vinyl ether copolymer. Examples of the nitrile rubber include an acrylonitrile-butadiene copolymer and an acrylonitrile-isoprene copolymer. Examples of the butadiene rubber include polybutadiene, acrylonitrile-butadiene-styrene copolymer, and methyl methacrylate-butadiene-styrene copolymer. The rubber compound may be a crosslinked rubber obtained by copolymerizing a crosslinkable monomer such as alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, or allyl (meth)acrylate with an acrylic acid ester as the main component.
[0048] The rubber compound is preferably a core-shell particle formed of a rubber layer of a core portion and an acrylic layer of a shell portion. This can improve the compatibility and dispersibility of the rubber compound in the (meth)acrylic polymer. The various rubber compounds described above can be used as the material of the rubber layer forming the core portion. The rubber compound may be a copolymer containing a conjugated diene such as butadiene or isoprene.
[0049] The acrylic material forming the acrylic layer of the shell portion may be a (meth)acrylic polymer containing at least one of (meth)acrylic acid ester, (meth)acrylic acid, (meth)acrylonitrile, etc., as a monomer. The acrylic material may be a methyl methacrylate copolymer or a methyl methacrylate homopolymer containing methyl methacrylate (MMA). The (meth)acrylic polymer may be a (meth)acrylic copolymer obtained by copolymerizing olefins such as ethylene, propylene, butadiene, isoprene, and styrene. The acrylic material may be a (meth)acrylic copolymer obtained by copolymerizing a monomer having a functional group such as a hydroxyl group, a carboxyl group, or a vinyl group.
[0050] The core-shell particles may have a structure in which the shell completely covers the periphery of the core, or a structure in which the shell only partially covers the periphery of the core. The shell may be formed around the core by coating and curing a resin, for example. The core-shell particle may have an intermediate layer between the core and shell. The intermediate layer may be omitted and the shell layer may be formed in contact with the core. The intermediate layer may have a transitional composition in which a rubber compound forming the core and an acrylic layer forming the shell layer are mixed. An adhesive layer between the core and shell may be laminated as the intermediate layer.
[0051] In the core-shell particle, the core and shell may be bonded via a chemical bond. For example, the resin forming the shell may be graft-polymerized onto the core by polymerizing a monomer forming the shell in the presence of a rubber compound particle forming the core. The core and shell may form an integral graft copolymer.
[0052] The method for producing the core-shell particles is not particularly limited, but for example, by proceeding with the polymerization of the core part by emulsion polymerization or the like until the desired diameter of the core part is reached, a particulate core part having high uniformity in shape, size, etc. can be formed. Furthermore, by proceeding with the polymerization of the shell part by emulsion polymerization or the like until the desired diameter of the shell part is reached, a particulate shell part having high uniformity in shape, size, etc. can be formed. When the core part and the shell part are bonded by graft polymerization, the core part and the shell part are firmly integrated via a chemical bond, so peeling of the shell layer can be suppressed.
[0053] The rubber compound is preferably particulate in the (meth)acrylic resin composition. When the (meth)acrylic resin composition is heat-molded, the rubber compound may maintain the shape of the particles, or the rubber compound may be melted and dispersed in the (meth)acrylic resin composition. The type of particle size of the rubber compound may be a volume-based average particle size that can be measured by a laser diffraction method or the like. The volume-based average particle size of the rubber compound is, for example, preferably 0.05 to 2.0 μm, more preferably 0.05 to 1.0 μm. When the rubber compound is a core-shell particle, the particle size of the core-shell particle includes the range of the shell part.
[0054] The rubber compound is preferably a core-shell particle formed of a rubber layer mainly made of styrene-butadiene rubber (SBR) or butadiene in the core portion and an acrylic layer mainly made of methyl methacrylate (MMA) in the shell portion, and the volume-based average particle diameter of the core-shell particle is preferably 0.05 to 2.0 μm, more preferably 0.05 to 1.0 μm.
[0055] The (meth)acrylic resin composition may be appropriately blended with known additives such as, but not limited to, the additives mentioned above, surfactants, curing accelerators, curing retarders, plasticizers, fillers, lubricants, processing aids, antioxidants, heat stabilizers, light stabilizers, antioxidants, antistatic agents, colorants, ultraviolet absorbers, infrared absorbers, etc. These additives may be used alone or in combination of two or more kinds.
[0056] The (meth)acrylic resin composition can be cured by reacting the (meth)acrylic polymer with the crosslinking agent after molding or coating into a predetermined shape. The molded product obtained from the (meth)acrylic resin composition is not particularly limited, but may be a film, a plate (sheet), a rod, or a fiber. The molding method of the molded product is not particularly limited, but may be cast molding, lamination molding, or extrusion molding. When the (meth)acrylic resin composition is applied onto a substrate, a resin film can be formed on the substrate by, for example, solution coating. The substrate is not particularly limited, but may be a resin film, a release film, a paper substrate, a metal foil, or a laminate.
[0057] When the crosslinking agent contained in the (meth)acrylic resin composition is a thermal crosslinking agent that initiates a crosslinking reaction by heating, it is preferable to fluidize the acrylic polymer as a solution of the (meth)acrylic resin composition rather than heating and melting it to fluidize it during molding of the molded product. The solvent for obtaining the solution of the (meth)acrylic resin composition is not particularly limited as long as it can dissolve the acrylic polymer without impairing the functional group of the acrylic polymer and the reactivity of the crosslinking agent. Examples of the solvent include hydrocarbon solvents such as toluene, alcohol solvents such as ethanol and isopropyl alcohol, ether solvents such as diethyl ether and tetrahydrofuran, ketone solvents such as acetone and methyl ethyl ketone (MEK), and ester solvents such as ethyl acetate. When the acrylic polymer is produced by a solution polymerization method, at least a part of the solvent used in polymerization may be at least a part of the solvent of the (meth)acrylic resin composition.
[0058] The (meth)acrylic resin film of this embodiment is characterized in that it is a resin layer formed by crosslinking the (meth)acrylic resin composition. The (meth)acrylic resin film can be produced, for example, by using a solution casting method to apply a solution of the (meth)acrylic resin composition onto a predetermined substrate to form a thin film, and then heat-drying the thin film to volatilize the solvent and crosslink the thin film. The substrate is not limited to a fixed flat surface, and examples include a resin film unwound from a roll of resin film, a movable belt, a drum, and the like. The surface property of the substrate is preferably a smooth surface, but it is also possible to transfer the unevenness to the surface of the (meth)acrylic resin film obtained by providing a predetermined unevenness on the substrate.
[0059] The (meth)acrylic resin film obtained by the solution casting method may be stretched in a predetermined direction such as the longitudinal direction or the width direction, or may be left unstretched. When it is necessary to reduce anisotropy in the use of an optical film, it is preferable to make the (meth)acrylic resin film into a non-stretched film. The (meth)acrylic resin film may be processed into a biaxially stretched film by stretching it in the longitudinal direction and the width direction. The anisotropy of the film is not limited to the anisotropy of mechanical properties such as "elongation at break", but also includes optical anisotropy such as "birefringence".
[0060] The mechanical properties of the (meth)acrylic resin film depend on the application, but when it is used as an adhesive sheet, an optical film, a surface protection film, a process film, etc., or when it is transported in the longitudinal direction, unwound from a roll, wound up onto a roll, etc., it is preferable that the (meth)acrylic resin film has a large number of folding cycles as folding resistance and a high tensile breaking strength as cut resistance, as well as a moderate breaking elongation as extensibility so as to obtain conformability to an adherend, etc.
[0061] The gel fraction of the resin layer constituting the (meth)acrylic resin film and obtained by crosslinking the (meth)acrylic resin composition is preferably 50% or more, more preferably 70% or more, even more preferably 90 to 100%, and particularly preferably 93 to 100%. By having such a high gel fraction of the resin layer, it is possible to improve the solvent resistance, which is a required physical property of the (meth)acrylic resin film.
[0062] The thickness of the (meth)acrylic resin film is not particularly limited, but for example, in the case of an optical film, the thickness is preferably about 10 to 200 μm, more preferably 10 to 50 μm, and particularly preferably 10 to 40 μm, and the film can also be made thin with a thickness of 40 μm or less. When another material is laminated on one or both sides of the (meth)acrylic resin film, the film may be subjected to a surface modification by corona discharge, a treatment for facilitating adhesion such as application of an anchor coating agent, etc., as necessary.
[0063] The (meth)acrylic resin film can improve bending resistance because the (meth)acrylic resin composition contains a rubber compound. When the (meth)acrylic resin film is measured according to JIS P8115 (paper and paperboard-folding endurance test method-MIT test machine method), the number of folding times as folding endurance is preferably 100 times or more, more preferably 200 times or more. Typical conditions for measuring the number of folding times include a method in which a test piece having a width of 15.0±0.1 mm and a length of about 110 mm is repeatedly folded back and forth at a load of 9.8 N at a speed of 175±10 times per minute. The number of folding times until the test piece breaks is measured as the number of folding times.
[0064] The (meth)acrylic resin film can improve deformability because the (meth)acrylic resin composition contains a rubber compound. The (meth)acrylic resin film has a breaking elongation percentage as an extensibility of preferably 10% or more, more preferably 20% or more. The breaking elongation percentage of films can be measured in accordance with standards such as JIS K7161 (Plastics - Determination of tensile properties) and JIS K7127 (Plastics - Test method for tensile properties).
[0065] The (meth)acrylic resin film may be used as a substrate for an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films. Examples of devices to which optical members are applied include liquid crystal panels, organic EL panels, and touch panels. When the (meth)acrylic resin film is used as an optical film, it is preferably colorless and transparent.
[0066] The (meth)acrylic resin film preferably has an in-plane retardation Re of 1.0 nm or less. The smaller the in-plane retardation Re, the more optically isotropic the (meth)acrylic resin film becomes, and the more the change in color tone can be suppressed when the (meth)acrylic resin film is attached to an optical device or used for optical inspection.
[0067] The (meth)acrylic resin film preferably has a haze value of 3.0% or less. The lower the haze value, the less light is scattered when passing through the (meth)acrylic resin film. For example, when the (meth)acrylic resin film is incorporated into an optical device such as a display, light leakage due to scattered light can be suppressed.
[0068] When measuring optical properties such as in-plane retardation Re and haze value for the purpose of comparing the optical properties of the (meth)acrylic resin compositions, the thickness of the (meth)acrylic resin film used for the measurement may be different from the thickness of the (meth)acrylic resin film to be manufactured. The thickness of the (meth)acrylic resin film used as the standard for the optical properties may be, for example, 20 to 30 μm, more specifically, 25 μm.
[0069] One or more of a hard coat layer, an antistatic layer, an antireflection layer, an antifouling layer, an antiglare layer, a low refractive index layer, an adhesive layer, a release layer, etc. may be laminated on one or both sides of the (meth)acrylic resin film. Examples of the fluorine compound used in the composition for forming the low refractive index layer include fluorine-containing copolymers which are polymers of one or more of fluorinated olefins, fluorinated vinyl ethers, fluorinated alkyl (meth)acrylates, etc., and condensates of fluorinated alkyl group-containing silane compounds. The fluorine-containing copolymer may be copolymerized with non-fluorinated monomers such as olefins, vinyl ethers, and (meth)acrylates in addition to fluorinated monomers. The low refractive index layer may be combined with a high refractive index layer to form an antireflection layer.
[0070] The adhesive sheet of the present embodiment is characterized in that an adhesive layer is formed on one or both sides of the (meth)acrylic resin film, which is a resin layer formed by crosslinking the (meth)acrylic resin composition. The adhesive layer is preferably an adhesive layer made of a (meth)acrylic adhesive. The adhesive layer may be formed on the (meth)acrylic resin film by a known method. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating can be used.
[0071] The pressure-sensitive adhesive sheet may be an optical film with a pressure-sensitive adhesive layer, which is formed by laminating a pressure-sensitive adhesive layer on at least one surface of an optical film having the (meth)acrylic resin film as a substrate. The optical film with a pressure-sensitive adhesive layer can be used for bonding optical films in various display devices such as liquid crystal display devices, touch panels, electronic paper, and organic EL. The adhesive surface of the adhesive layer used for bonding the optical film may be protected by a release film. The release film may be subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface that is to be joined to the adhesive surface of the adhesive layer.
[0072] The pressure-sensitive adhesive sheet may constitute a surface protection film that is attached via the pressure-sensitive adhesive layer to protect the surface of an adherend such as glass, an optical film, an optical member, etc. With the surface protection film attached to the adherend, the optical properties of the adherend, the presence or absence of foreign matter, etc. can be optically inspected. In addition, at the stage of incorporating the adherend into a product, the surface protection film can be peeled off and removed from the adherend.
[0073] The polarizing film of the present embodiment is characterized in that the (meth)acrylic resin film, which is a resin layer obtained by crosslinking the (meth)acrylic resin composition, is formed on one or both sides of a polarizer. The surface treatment applied to the surface of the protective layer of the polarizer may be at least one selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment. Here, AG stands for anti-glare, LR stands for low reflection, and AR stands for anti-reflection.
[0074] Examples of the protective layer of the polarizer include acrylic resins such as triacetyl cellulose (TAC) and polymethyl methacrylate (PMMA), polyester resins such as polyethylene terephthalate (PET), cyclic olefin polymers, polycarbonates, etc. The (meth)acrylic resin film may be attached to the protective layer of the polarizer via the adhesive layer of the adhesive sheet. In addition, the (meth)acrylic resin film, which is a resin layer formed by crosslinking the (meth)acrylic resin composition of the present embodiment, can also be used as the protective layer of the polarizer. EXAMPLES
[0075] The present invention will now be described in detail with reference to examples.
[0076] <Production of (meth)acrylic polymer and (meth)acrylic resin composition> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 95 parts by weight of methyl methacrylate, 5 parts by weight of methyl acrylate, 3.0 parts by weight of 8-hydroxyoctyl methacrylate, and a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile was dropped as a polymerization initiator, and the mixture was heated to 65°C and reacted for a predetermined time to obtain a (meth)acrylic polymer solution of Example 1. The weight average molecular weight (Mw) of the (meth)acrylic polymer contained in this (meth)acrylic polymer solution was measured and found to be 200,000. To the (meth)acrylic polymer solution of Example 1, 10 parts by weight of Kaneace (registered trademark) M-230 as a rubber compound and 3.0 parts by weight of Coronate (registered trademark) HX as a crosslinking agent were added and stirred and mixed, to obtain a (meth)acrylic resin composition of Example 1.
[0077] [Examples 2 to 7 and Comparative Examples 1 to 3] The (meth)acrylic polymers and (meth)acrylic resin compositions of Examples 2 to 7 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the compositions of the (meth)acrylic polymer and (meth)acrylic resin composition of Example 1 were respectively as shown in Table 1. The weight average molecular weights (Mw) of the (meth)acrylic polymers of Examples 2 to 7 and Comparative Examples 1 to 3 were as shown in Table 1.
[0078] [Comparative Example 4] A commercially available PMMA film (thickness: 80 μm) produced by melt extrusion was dissolved in methyl ethyl ketone (MEK) as a solvent, and the weight average molecular weight (Mw) of the polymer contained in the PMMA film was measured and found to be 300,000.
[0079] [Table 1]
[0080] In Table 1, the value in parts by weight calculated assuming the total of the monomers in group (A) to be 100 parts by weight is shown next to the abbreviation corresponding to the compound name. The meanings of the abbreviations (compound names, etc.) used in Table 1 are as follows:
[0081] [Monomers of group (A)] "MMA": Methyl methacrylate "MA": Methyl acrylate "TBA": t-butyl acrylate "BMA": n-butyl methacrylate "EMA": Ethyl methacrylate "IBMA": Isobutyl methacrylate
[0082] [Monomers of group (B)] "8HOA": 8-hydroxyoctyl acrylate "8HOMA": 8-hydroxyoctyl methacrylate "6HHA": 6-hydroxyhexyl acrylate "6HHMA": 6-hydroxyhexyl methacrylate "4HBMA": 4-hydroxybutyl methacrylate "HEA": 2-hydroxyethyl acrylate "HEMA": 2-hydroxyethyl methacrylate "Aac": acrylic acid
[0083] [Rubber compounds] The particle sizes shown below are all volume-based average particle sizes. "M-230": Kane Ace (registered trademark) M-230 (core-shell particle, particle size: 0.1 μm, core part: SBR, shell part: MMA, product name of Kaneka Corporation) "M-210": Kane Ace (registered trademark) M-210 (core-shell particle, particle size: 0.2 μm, core part: SBR, shell part: MMA, product name of Kaneka Corporation) "B-513": Kane Ace (registered trademark) B-513 (core-shell particle, particle size: 0.2 μm, core part: butadiene, shell part: MMA, product name of Kaneka Corporation) "LP-4100": Metablen (registered trademark) LP-4100 (acrylic rubber particles, particle diameter: 1 μm, product name of Mitsubishi Chemical Corporation)
[0084] [Crosslinking agent] "HX": Coronate (registered trademark) HX (HDI isocyanurate, trade name of Tosoh Corporation) "HL": Coronate (registered trademark) HL (HDI adduct, trade name of Tosoh Corporation) "D-140N": Takenate (registered trademark) D-140N (IPDI adduct, product name of Mitsui Chemicals, Inc.) "TX": TETRAD (registered trademark)-X (a tetrafunctional epoxy compound, a trade name of Mitsubishi Gas Chemical Company, Inc.)
[0085] <Preparation of (meth)acrylic resin film> The (meth)acrylic resin compositions of Examples 1 to 7 and Comparative Examples 1 to 3 were formed into resin films by a solution casting method, and then heated and dried under temperature conditions suitable for drying the solvent and curing the crosslinking agent, and crosslinked to obtain the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 3. The thickness (μm) of each film is shown in Table 2. As the (meth)acrylic resin film of Comparative Example 4, a commercially available PMMA film (thickness: 80 μm) produced by the melt extrusion method was used as described above.
[0086] <Test methods and evaluation of (meth)acrylic resin films> The (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4 were evaluated by the following test methods.
[0087] <Haze value> Test pieces were prepared from the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4, and the haze value (%) was measured using a haze meter (manufacturer: Nippon Denshoku Co., Ltd., model: Haze Meter, NDH2000).
[0088] <Number of times folded as folding durability> Test pieces were prepared from the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4, and then a folding endurance test was performed using a folding endurance tester (manufacturer: Tester Sangyo Co., Ltd., model: MIT folding endurance tester BE-201) in accordance with JIS P8115 (paper and paperboard--folding endurance test method--MIT tester method), and the number of reciprocating folds (fold endurance number) until the test piece broke was measured.
[0089] <Gel fraction as a measure of solvent resistance> As a method for testing the solvent resistance, a test piece of the (meth)acrylic resin film was immersed in a solvent liquid for a predetermined time as described below, and then the proportion of the (meth)acrylic resin film that was not dissolved in the solvent and remained as an insoluble portion (residue) (so-called gel fraction) was measured to test the solvent resistance. Test pieces were prepared from the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4, and the masses of the test pieces were accurately measured, and the test pieces were immersed in methyl ethyl ketone (MEK) for 24 hours, and then filtered through a 200-mesh wire screen. The filtered material was then dried at a temperature of 100°C for 1 hour, and the mass of the resulting residue was accurately measured, and the gel fraction (%) due to immersion in a solvent was measured as a method for testing solvent resistance according to the following formula. Gel fraction (%) = insoluble matter (residue) mass (g) / film (test piece) mass (g) × 100
[0090] <Tensile breaking strength as cut resistance, breaking elongation as extensibility> Test pieces were prepared from the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4, and were measured using a tensile testing device (manufacturer: Shimadzu Corporation, model: AGS-X) to determine the tensile breaking strength (MPa) as the cut resistance until the test piece broke, and the breaking elongation (%) as the extensibility.
[0091] <Retardation (in-plane retardation Re value)> The in-plane retardation (Re) values (nm) of the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4 were measured using a retardation measurement device (manufacturer: Oji Scientific Instruments Co., Ltd., model: KOBRA-HBPR / SPC). The wavelength for measuring the retardation can be appropriately selected from the visible range, for example, 450 to 550 nm. The Re value is calculated by dividing the refractive index n in the x-axis direction by the refractive index in the x-axis direction (slow axis) when the direction perpendicular to the x-axis is the x-axis (slow axis) and the direction perpendicular to the x-axis is the y-axis (fast axis). x and the refractive index in the y-axis direction, n y and the film thickness d, it is calculated by the following formula. In-plane phase difference Re=(n x -n y )×d Here, the film thickness d of the film is expressed in nm units like the in-plane retardation Re, and is 1000 times the film thickness (μm).
[0092] Table 2 shows the evaluation results for the (meth)acrylic resin films of Examples 1 to 7 and Comparative Examples 1 to 4.
[0093] [Table 2]
[0094] The (meth)acrylic resin films of Examples 1 to 5 were formed into thin films having a thickness of 40 μm or less, with a haze value of 3.0% or less, folding resistance as a folding endurance of 200 times or more, solvent resistance as a gel fraction of 90% or more, cut resistance as a tensile breaking strength of 40 MPa or more (about 50 MPa or more), elongation at break as a breaking elongation of 20% or more, and an in-plane retardation Re of 1.0 nm or less. Thus, the (meth)acrylic resin films of Examples 1 to 5 were excellent in all physical properties.
[0095] The (meth)acrylic resin film of Example 6 was formed into a thin film having a thickness of 40 μm or less, and although the haze value was somewhat high, the folding resistance was 200 times or more, the solvent resistance was 90% or more in gel fraction, the cut resistance was 50 MPa or more in tensile breaking strength, the elongation at break was 20% or more, and the in-plane retardation Re was 1.0 nm or less. Thus, the (meth)acrylic resin film of Example 6 was excellent in all physical properties.
[0096] The (meth)acrylic resin film of Example 7 was formed into a thin film having a thickness of 40 μm or less, and although it had a high haze value, it had a folding resistance of 100 times or more, a solvent resistance of 90% or more in gel fraction, a cut resistance of 50 MPa or more in tensile breaking strength, an extensibility of 10% or more in breaking elongation, and an in-plane retardation Re of 1.0 nm or less. Thus, the (meth)acrylic resin film of Example 7 was excellent in all physical properties.
[0097] In this manner, it has been demonstrated that the (meth)acrylic resin films of Examples 1 to 7 are capable of solving the problems of the present invention.
[0098] The (meth)acrylic resin film of Comparative Example 1 had a low number of folding cycles as a folding resistance, possibly because the (meth)acrylic resin composition did not contain a rubber compound. When Example 7 and Comparative Example 1 are compared with respect to the presence or absence of a rubber compound, the number of folding cycles as a folding resistance is more than twice as high as that of Comparative Example 1, even though the breaking elongation percentage as a folding resistance is approximately the same for Comparative Example 1 and Example 7.
[0099] In the (meth)acrylic resin film of Comparative Example 2, the (meth)acrylic polymer was copolymerized with only MMA as the alkyl (meth)acrylate having an alkyl group with a carbon number of C1 to C14. The Tg of the homopolymer was 0°C or higher, and no alkyl (meth)acrylate having an alkyl group with a carbon number of C1 to C14 other than MMA was copolymerized. Perhaps because of this, the number of folding cycles as a measure of folding resistance was low, and the elongation at break as a measure of extensibility was extremely low.
[0100] The (meth)acrylic resin film of Comparative Example 3 had a low number of folding cycles as a measure of folding resistance and an extremely low gel fraction as a measure of solvent resistance, possibly because the (meth)acrylic resin composition did not contain a rubber compound or a crosslinking agent. The extremely low gel fraction as a measure of solvent resistance is believed to be due to the fact that the (meth)acrylic resin composition was not crosslinked by a crosslinking agent.
[0101] The (meth)acrylic resin film of Comparative Example 4 was a resin film produced by melt extrusion, but had a small number of folding cycles as a folding resistance, an extremely low gel fraction as a solvent resistance, and a large in-plane retardation Re. The extremely low gel fraction as a solvent resistance is believed to be due to the fact that the resin film produced by melt extrusion was not crosslinked by a crosslinking agent.
[0102] In addition, assuming that the thickness of the (meth)acrylic resin film of Comparative Example 4 is 20 μm, the Re value is 1 / 4 according to the thickness ratio (20 / 80). However, since the Re value is still large, the birefringence (n x -n y ) itself is considered to be large.
[0103] As described above, the (meth)acrylic resin films of Comparative Examples 1 to 4 were unable to achieve the objective of the present invention of providing a (meth)acrylic resin film having excellent folding resistance, cut resistance, elongation, and solvent resistance. [Industrial Applicability]
[0104] The (meth)acrylic resin composition of the present invention and the (meth)acrylic resin film using the same have excellent physical properties, particularly in terms of thinning, folding resistance and solvent resistance, compared with (meth)acrylic resin films obtained by conventional melt extrusion methods. Therefore, they are expected to be effective in reducing the thickness and improving the durability of various optical devices such as displays, and therefore have great industrial utility value.
Claims
1. A (meth)acrylic resin film comprising a resin layer crosslinked from a (meth)acrylic resin composition containing a (meth)acrylic polymer, a rubber compound, and a crosslinking agent, The (meth)acrylic resin composition is a solution of the (meth)acrylic resin composition used in a solution casting method, The (meth)acrylic polymer is As the monomer of group (A), methyl methacrylate and at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0° C. or higher and the alkyl group has a carbon number of C1 to C14; (B) at least one selected from the group consisting of copolymerizable monomers having a hydroxyl group and copolymerizable monomers having a carboxyl group as a copolymerizable monomer having a functional group capable of reacting with the crosslinking agent; is a (meth)acrylic polymer copolymerized with The (meth)acrylic resin film has an in-plane retardation Re of 1.0 nm or less and a haze value of 3.0% or less.
2. The (meth)acrylic resin film according to claim 1, characterized in that the monomer of group (A) is 100 parts by weight in total of 80 to 99 parts by weight of methyl methacrylate and 1 to 20 parts by weight of at least one alkyl (meth)acrylate other than the methyl methacrylate, the homopolymer of which has a Tg of 0°C or higher and the alkyl group has a carbon number of C1 to C14.
3. 3. The (meth)acrylic resin film according to claim 1, wherein the rubber compound is a core-shell particle formed of a rubber layer mainly made of SBR or butadiene in a core portion and an acrylic layer mainly made of methyl methacrylate in a shell portion, and the core-shell particle has a volume-based average particle diameter of 0.05 to 2.0 μm.
4. The (meth)acrylic resin film according to any one of claims 1 to 3, characterized in that the copolymerizable monomer having a hydroxyl group is at least one selected from the group of compounds consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide, and further contains at least one selected from the group of compounds consisting of 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl methacrylate, 4-hydroxybutyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
5. The (meth)acrylic resin film according to any one of claims 1 to 4, wherein the (meth)acrylic resin film has a thickness of 10 to 50 µm.
6. The (meth)acrylic resin film according to any one of claims 1 to 5, characterized in that the (meth)acrylic resin film has a gel fraction of 90% or more as a solvent resistance, a folding endurance of 100 times or more (JIS P8115) as a folding endurance, and a breaking elongation of 10% or more as an extensibility.
7. 7. A pressure-sensitive adhesive sheet comprising the (meth)acrylic resin film according to claim 1 and a pressure-sensitive adhesive layer formed on one or both sides of the (meth)acrylic resin film.
8. A polarizing film comprising the (meth)acrylic resin film according to any one of claims 1 to 6 formed on one or both sides of a polarizer.
Citation Information
Patent Citations
Production of reactive resin sheet
JP1997141718A
Polarizer protective film and polarizing plate
JP2013182070A
Optical film and method for manufacturing the same, polarizing plate protective film, polarizing plate, and liquid crystal display device
JP2016042159A
Optical film and method of manufacturing polarizing plate using the same
JP2020071449A
Method for manufacturing acrylic film
WO2020067218A1